The Prevalence of Schistosomasis among People in Almatama locality River Nile State, Sudan - Ahmed, M. Hussein; Dawria., Adam; Suleman, Alkamil; Belal, Abdallah A. Adam (Journal of Clinical Research In HIV AIDS And Prevention, 2019)
This is cross sectional descriptive community based study to measure the prevalence of Schistosomasis disease, multistage cluster sampling was taken (500person), and the data was collected by the flowing methods, Urine Examination, Stool examination, and Questionnaire, the data was analyzed by using (SPSS) the main result for study Schistosomosis Hematoupium was 15% and Schistosomosis Mansoni was Zero, the prevalence was high in Tibaha Alkhwad administrative unit with 6.0%, Almata with 5.2% and Wedhamid with 3.8%. The study found there was strong relation between Shistosomasis and both genders (male, female) where the prevalence was high among male 10.8%, the study also showed there was strong relationship between Schistosomasis and age groups, The prevalence increases among age group (15 to 25 years )with (5.8%), There was strong significant relation between swimming in stagnant water and getting infected with Schistosomasis, The prevalence increases among people go to swimming in stagnant water with 11.0% (PV =0.0000 significant),